Factors associated with patient visits to the emergency department for asthma therapy in Pakistan. Issue 1 (December 2016) - Bilal, Muhammad; Haseeb, Abdul; Khan, Mohammad; Saad, Muhammad; Devi, Sapna; Arshad, Mohammad; Alam, Anusha; Wagley, Abdullah; Javed, Khawaja
Abstract Background Acute asthma is a chronic condition affecting people of all ages around the world and hence, is one of the leading causes of emergency department (ED) visits and hospital admissions globally. Most of them are related to poor patient practices and a weak healthcare system. The aim of our study was to assess the reasons for the increased usage of the ED by asthmatic patients in Pakistan. Methods A cross-sectional study was conducted on 600 asthmatic patients reporting to the ED of Civil Hospital Karachi over a 6-month period. The consenting patients were given a questionnaire to fill and the following data was collected: demographic information, duration of the disease, medications prescribed the, frequency of and reasons for outpatient clinic and ED visits for issues related to asthma. Result According to our results most of the participants visited the ED to obtain a nebulized bronchodilator (90 %) or oxygen (79.5 %). Moreover, 44.8 % of the people visited the ED to get treatment without any delay and 24.0 % considered that the severity of asthma does not allow the patient to wait for clinic visits. Strikingly, 92.8 % claimed that inhaled corticosteroid therapy treatment should be stopped when patients feel better. Irregular follow ups with clinics, low education about asthma and an education level higher than a Bachelors degree were the most important factors associated with three or more ED visits per year, p values = 0.0289, 0.0110 and 0.0150 respectively. Conclusion This study identifies several preventable risk factors responsible for recurrent visits to the ED by asthmatic patients in Pakistan.